Microcontroller – Based Plotter Machine - Nsayef, Aman Ismail; Mahmood, Anas Lateef (Al-Nahrain Journal for Engineering Sciences, 2018)
The main idea behind this paper is to design and implement a cheap, smaller size, easily operable, easy interface and flexible 3-axis Computer Numerical Control (CNC) plotter machine. The lower cost is achieved by using 2 CD drives from old PC’s with their stepper motors as the main structure for the hardware. The two stepper motors already found in the CD drives used to control the pen movements onto X and Y axis and one servo motor on the Z axis. An Arduino Uno microcontroller is used to controls the proper synchronization of these three motors during printing/drawing process. The Arduino Uno is programmed with G-Code parser from PC that is connected to the Arduino via a USB cable to control the motors movement and synchronization. The plotter machine is implemented and tested by printed different images and texts on papers (8cm × 8cm) using a pen, the small size of the papers because of the small plotter size. The motors winding voltages were displayed on the oscilloscope during the printing process to investigate the synchronization between the three motors. The design of the circuit is simple, inexpensive and can be accomplished using commercially available components.